Mathematical Skills and General Mathematics Performance of Grade 11 Students in a Public National High School in Southern Negros Occidental, Philippines - Parcon, Cleah Amor S.; Bearneza, Francis Jose D. (Philippine Social Science Journal, 2025)
This quantitative study assesses the relationship between mathematical skills and General Mathematics performance among 278 Grade 11 students in a southern Negros Occidental public high school. Using descriptive, comparative, and correlational designs, the results indicate that while students are "approaching proficient" in fundamental skills, their actual subject performance remains at a "developing" level. The analysis reveals significant variations in skills based on sex and academic strand, confirming a strong link between mathematical proficiency and academic performance. These findings underscore the need for supplementary instructional materials to bridge the gap between foundational knowledge and application, providing a basis for curriculum enhancements and broader future research.